Fournier's gangrene current approaches1. Issue 5 (22nd August 2014) - Ozkan, Omer F; Koksal, Neset; Altinli, Ediz; Celik, Atilla; Uzun, Mehmet A; Cıkman, Oztekin; Akbas, Alpaslan; Ergun, Ersin; Kiraz, Hasan A; Karaayvaz, Muammer
Abstract: Fournier's gangrene is a rare but highly mortal infectious disease characterised by fulminant necrotising fasciitis involving the genital and perineal regions. The objective of this study is to analyse the demographics, clinical feature and treatment approaches as well as outcomes of Fournier's gangrene. Data were collected retrospectively from medical records and operative notes. Patient data were analysed by demographics, aetiological factors, clinical features, treatment approaches and outcomes. Twelve patients (five female and seven male) were enrolled in this study. The most common aetiology was perianal abscess (41·6%). Wound cultures showed a mixture of microorganisms in six (50%) patients. For faecal diversion, while colostomy was performed in six cases (50%), Flexi‐Seal was used in two cases (16·6%). In four patients (33·4%), no faecal diversion was performed. Negative pressure wound therapy (NPWT) system was effective in the last four patients (33·4%). The mean hospitalisation period in patients who used NPWT was 18 days, while it was 20 days in the others. NPWT in Fournier's gangrene is a safe dressing method. It promotes granulation formation. Flexi‐Seal faecal management is an alternative method to colostomy and provides protection from its associated complications. The combination of two devices (Flexi‐Seal and NPWT) is an effective and comfortable method in the management of Fournier's gangrene in appropriate patients.